Die Larven der europäischen Arten der Gattung Xylophagus Meigen (Diptera: Xylophagidae). - Krivosheina, Nina P.; Mamajev, Boris M. (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The larvae of the species of the genus Xylophagus Meigen live under the bark and in decaying wood. They prey on nearly all insect larvae to be found in wood, and on earth-worms. - The larvae of X. ater Meigen live deep in the wood of deciduous trees, those of X. cinctus Degeer under the bark of conifers, and those of X. compeditus Wiedemann under the bark of both deciduous and coniferous trees. - In previous publications the larvae of X. compeditus Wiedemann were taken for the larvae of X. ater Meigen. The present paper characterizes the larvae of X. compeditus Wiedemann and X. cinctus Degeer and gives a first description of the larvae of X. ater Meigen .